Intangible assets innovation through Health Technology Assessment. The case of the Italian Healthcare Organisations - Tallarico, Salvatore; Occhipinti, Zeila; Lazzini, Simone; Pellegrini, Luisa (Mecosan - Management ed Economia Sanitaria - Open Access, 2023)
The use of Health Technology Assessment (HTA) for the evaluation of medical devices in healthcare organisations implies the creation of new knowledge to be combined with that stored in the human, relational, and structural dimensions of their Intellectual Capital (IC). Therefore, HTA can represent a trigger for innovating the IC and this process can be influenced by external factors that can be reconducted to the Institutional Theory (IT). However, to the best of our knowledge, there are no studies in the literature analysing these aspects. By using the case study methodology, this work explores how the innovation of the IC dimensions is triggered by the use of the HTA tools, considering also the moderating role of the IT pillars.